Cross-National Work-Life Research: Cultural and Structural Impacts for Individuals and Organizations. (January 2017) - Ollier-Malaterre, Ariane; Foucreault, Annie
Increasing attention is being paid to the impacts of country-level contexts on the work-life interface. However, lack of theoretical clarity as well as operationalization challenges are significant roadblocks for comparative work-life research. This article provides guidance for cross-national work-life research by conducting a systematic interdisciplinary review of conceptual and empirical work on the country-level cultural impacts (i.e., the values, assumptions, and beliefs shared by individuals with common historical experience) and structural impacts (i.e., the rules and constraints produced by legal, economic, and social structures) on individual experiences of the work-life interface and organizational support for nonwork. Regarding culture, we offer an organized review of work-life research drawing on cultural dimensions, from the most researched dimensions, such as individualism-collectivism and gender egalitarianism, to the least researched. We also point to ways to locate scales and country scores. Concerning structure, we explain how legal (e.g., public policies), economic (e.g., industrialization), and social (e.g., actual gender equality) factors are operationalized with indicators or typologies and review the related work-life research. We carve out a research agenda pointing out untapped cultural dimensions and structural factors and underresearched work-life constructs and calling for more systemic and integrative cross-national work-life research.